Pengaruh Dukungan Sosial Teman Sebaya Terhadap Tingkat Kepercayaan Diri Mahasiswa Saat Presentasi di Kelas - Araminta, Karin Ardelia; Izzati, Nur Amalina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aimed to analyze the relationship between peer social support and the confidence level of Islamic Guidance and Counseling students during classroom presentations. Peer social support includes emotional support, as it is considered one of the important factors that can affect individuals’ self-confidence. Whereas, the self-confidence level was analyzed based on Albert Bandura’s self-efficacy theory which included indicators of mastery experience, vicarious experience, social persuasion, and psychological and emotional. Self-efficacy occupies an important and influential role in human life, a person will be able to use their potential optimally when their self-efficacy is high. The study used a quantitative research method to measure the relationship between social support and students’ confidence levels. The results of the study showed that there was a positive and significant relationship between peer social support and students’ self-confidence level. The conclusion of this study is that the social support that students receive from their peers, affects their level of confidence while doing presentations in class.